MAPPING ENABLERS AND CHALLENGES OF TILAPIA WOMEN FARMERS IN ENHANCING FOOD SECURITY THROUGH ACCELERATED DIGITAL TRANSFORMATION IN SLEMAN REGENCY, SPECIAL REGION OF YOGYAKARTA, INDONESIA - Prihatiningtyastuti, Endah; Dayaram, Kantha; Saksono, Hery; Suadi, Suadi; Shafira, Azellia Alma; Cahyani, Aulia Putri Nur; Paramitha, Dinda Laksmi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2025)
This study investigates the enablers and challenges of digital transformation for women tilapia farmers in Sleman Regency, aiming to understand its role in enhancing food security. The research employed qualitative approaches, including document analysis, focus group discussions, and in-depth interviews with 28 informants, conducted in Sleman Regency, Yogyakarta, Indonesia. Findings reveal that women farmers in the 'Mina Mandiri' group effectively leverage digital technologies to boost productivity and market.  Reach. Key enablers include strong support from local resources, family, and community networks. Despite these enablers, they are still facing structural hurdles, including restricted access to education, inadequate computer literacy, and the absence of gender-responsive regulations, compounded by cultural impediments associated with gender roles and male dominance in the sector. The study underscores the critical need for gender-responsive strategies to overcome these obstacles and fully harness the potential of digital transformation, thereby significantly enhancing food security through the empowerment of women tilapia farmers.